Cumulative response of ecosystem carbon and nitrogen stocks to chronic CO2 exposure in a subtropical oak woodland. Issue 3 (30th May 2013) - Hungate, Bruce A.; Dijkstra, Paul; Wu, Zhuoting; Duval, Benjamin D.; Day, Frank P.; Johnson, Dale W.; Megonigal, J. Patrick; Brown, Alisha L. P.; Garland, Jay L.
Summary Rising atmospheric carbon dioxide (CO2) could alter the carbon (C) and nitrogen (N) content of ecosystems, yet the magnitude of these effects are not well known. We examined C and N budgets of a subtropical woodland after 11 yr of exposure to elevated CO2. We used open‐top chambers to manipulate CO2 during regrowth after fire, and measured C, N and tracer 15N in ecosystem components throughout the experiment. Elevated CO2 increased plant C and tended to increase plant N but did not significantly increase whole‐system C or N. Elevated CO2 increased soil microbial activity and labile soil C, but more slowly cycling soil C pools tended to decline. Recovery of a long‐term 15N tracer indicated that CO2 exposure increased N losses and altered N distribution, with no effect on N inputs. Increased plant C accrual was accompanied by higher soil microbial activity and increased C losses from soil, yielding no statistically detectable effect of elevated CO2 on net ecosystem C uptake. These findings challenge the treatment of terrestrial ecosystems responses to elevated CO2 in current biogeochemical models, where the effect of elevated CO2 on ecosystem C balance is described as enhanced photosynthesis and plant growth with decomposition as a first‐order response.